2009
DOI: 10.1182/blood-2008-03-147892
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the BMP4-dependent stress erythropoiesis pathway in the murine spleen requires hedgehog signaling

Abstract: The production of mature cells necessitates that lineage-committed progenitor cells be constantly generated from multipotential progenitors. In addition, the ability to respond rapidly to physiologic stresses requires that the signals that regulate the maintenance of progenitor populations be coordinated with the signals that promote differentiation of progenitors. Here we examine the signals that are necessary for the maintenance of the BMP4-dependent stress erythropoiesis pathway. Our previous work demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 42 publications
4
110
1
Order By: Relevance
“…111,112 For BFU-E cells to be responsive to BMP4, they need to be "primed" with Sonic Hedgehog, a morphogen that is also synthesized and secreted by cells in the spleen microenvironment. 113 BMP4, in turn, activates the transcription factor Smad5 as well as Scl and Gata2, which enhances the probability of BFU-E self-renewal over differentiation (Figure 3). 84,114,115 …”
Section: Bmp4mentioning
confidence: 99%
“…111,112 For BFU-E cells to be responsive to BMP4, they need to be "primed" with Sonic Hedgehog, a morphogen that is also synthesized and secreted by cells in the spleen microenvironment. 113 BMP4, in turn, activates the transcription factor Smad5 as well as Scl and Gata2, which enhances the probability of BFU-E self-renewal over differentiation (Figure 3). 84,114,115 …”
Section: Bmp4mentioning
confidence: 99%
“…Given this, we examined the effect of reducing environmental Hh protein in the spleen on Th2 differentiation of nontransgenic CD4 + cells ex vivo. We used Dhh KO CD4 splenocytes, as Dhh is expressed by spleen stroma (40) and, unlike Shh KO, is not an embryonic-lethal mutation. We cultured Dhh KO and WT cells in Th2 skewing conditions and found that Dhh KO cells upregulate Gata3 less efficiently than do WT cells after stimulation (Fig.…”
Section: Repressing Physiological Hh Inhibits Th2mentioning
confidence: 99%
“…enzymes and factors involved in anti-oxidant signaling), there is a host of other genetically impaired pathways that compromise terminal erythroid differentiation or influence erythropoietin (Epo)-responses, especially after stress. [15][16][17][18][19][20][21][22] In the great majority of these cases, attempts to compensate for RBC losses lead to an increase in erythropoiesis at early stages (ineffective erythropoiesis) and to splenomegaly in mice.…”
Section: Introductionmentioning
confidence: 99%
“…During stress, bone morphogenetic protein 4/hedgehog signaling and hypoxia are necessary for expanding a specific subset of progenitors within the murine splenic environment to quickly address stress demands for RBC production. 17,18,20 Since the ability of these special progenitor cells to respond to stress depends on cues from the microenvironment (ME) of the spleen rather than the bone marrow (BM), distinct erythroid cell/ME interactions are apparently at play in the former but not the latter environment under stress. Although the spleen has been recognized as the favored ME for stress response in the mouse, the specific ME/hematopoietic cell interactions responsible for the differences between BM and spleen environment have not been defined.…”
Section: Introductionmentioning
confidence: 99%